Industrial Compliance with Social Legislation: Investigations of Decision Rationales - Greer, Charles R.; Downey, H. Kirk (Academy of Management Review, 1982)
A model of compliance behavior and a research paradigm for testing the model's validity in organizational settings are presented. The model seeks to determine whether compliance decisions are based on normative or calculative criteria and whether such rationales are individual or organizational in origin. Studies that have tested the model are reviewed. They provide support for the general approach and also insight into specific legislation decision rationales.